Rectal malakoplakia mimicking advanced rectal cancer: A case report - Xiangyu Liu; Chenming Yu; Zhuo Zhao; Yiping Zheng; Xin Chen; Dandan Zhou (Heliyon, 2023)
Background: Malakoplakia is a rare acquired chronic infectious granulomatous condition, that is characterized by the accumulation of large granular macrophages containing basophilic inclusion bodies in the cytoplasm termed Michaelis-Gutmann (MG) bodies. Malakoplakia most commonly involves the genitourinary system, and the second most commonly affected site is the gastrointestinal tract. Rectal malakoplakia is an unusual entity that is difficult to diagnose due to its diverse clinical manifestations and radiological findings that are similar to different diseases and advanced cancers. Case description: A 61-year-old male patient presented with difficulty in urination and defecation that started 4 months prior, along with a weight loss of 10 kg. Abdominal computerized tomography (CT) scanning revealed diffuse lesions of the perirectal region with multiple lymphadenopathies and involvement of the bladder, prostate, bilateral seminal vesicles, and left ureter. 18F-FDG PET/CT MIP showed intense FDG uptake in the rectal region, and a diagnosis of an occupying lesion was proposed. Colonoscopy and histological examination of rectal lesion biopsies showed the characteristic features of malakoplakia. Conclusion: Malakoplakia of the rectum with lymph node involvement and adjacent organ extension has been extensively misdiagnosed in clinical practice, and mimics malignancy radiologically. It is of great importance for radiologists to be aware of malakoplakia when making the differential diagnosis of benign and malignant mass lesions of the rectum, although the radiologic findings are nonspecific. Endoscopic evaluation and pathologic examination of a biopsy should be recommended to make the correct diagnosis, which may prevent unnecessary surgical resection.